Boundary faceting in Goss orientated nickel with a nanolaminated structure. (1st July 2018) - Xie, H.; Zhang, H.W.; Lu, K.
Abstract: Nanolaminated structure was fabricated in pure nickel with Goss orientation via dynamic plastic deformation and subsequent cold rolling, and the structural coarsening during post annealing was investigated. Local faceting of lamellar boundaries that are typical high angle boundaries with misorientation angle larger than 15° is observed during annealing. The facets are roughly parallel to the traces of {111} planes and more readily occur for boundaries misoriented from 15 to 40°. The local faceting of lamellar boundaries leads to structural coarsening and polygonization of lamellar structure. Graphical abstract: Unlabelled Image